Ecological hazards in the Himalyas - Chadha, S. K. (Jaipur, 1989)
The present book is written with the objective of creating environmental awareness among the masses and to suggest how the ecological balance can be maintained. To-day the Himalayas are under environmental threat and this challenge has to be faced.
Keywords: Ecology himalayas